2020
DOI: 10.1021/acs.inorgchem.0c02933
|View full text |Cite
|
Sign up to set email alerts
|

PrVO4 under High Pressure: Effects on Structural, Optical, and Electrical Properties

Abstract: In pursue of a systematic characterization of rare-earth vanadates under compression, in this work we have studied the phase behavior of zircon-type orthovanadate PrVO4 under high pressure conditions, up to 24 GPa, by means of powder x-ray diffraction. We have found that PrVO4 undergoes a zircon to monazite transition around 6 GPa, confirming previous results found on Raman experiments. A second transition takes place above 14 GPa, to a BaWO4-IItype structure. The zircon to monazite structural sequence is an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Beyond 6.0 GPa, the Raman peak assigned to the zircon structure completely disappears. This can be explained as the consequence of the zircon-to-monazite phase transition, as it has been reported in literature [13,14,16]. However, the Raman peaks of the monazite phase are too weak to be distinguished, so they become imperceptible hereon.…”
Section: Mode Theory Experimentsmentioning
confidence: 57%
See 2 more Smart Citations
“…Beyond 6.0 GPa, the Raman peak assigned to the zircon structure completely disappears. This can be explained as the consequence of the zircon-to-monazite phase transition, as it has been reported in literature [13,14,16]. However, the Raman peaks of the monazite phase are too weak to be distinguished, so they become imperceptible hereon.…”
Section: Mode Theory Experimentsmentioning
confidence: 57%
“…(S. G.: I41/a, Z = 4) [7][8][9][10], while those with larger cations (R = Ce, Pr) transform into a monazite-type phase (S. G.: P21/n, Z = 4) [11][12][13][14]. However, it has been suggested that some factors such as hydrostaticity or kinetic barriers can play a very important role both in the transition pressure and the structural sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 is the result for PrVO 4 (mp-19169 on the Materials Project [52]), which has a zircon-type structure and has attracted attention due to its redox activity as photocatalyst [64][65][66]. Its space group I4 1 {amd was retrieved as the second scored one.…”
Section: Retrieval Accuracies Of Space Group and Local Atomic Environ...mentioning
confidence: 99%
“…is the result for PrVO 4 (mp-19169 on the Materials Project), which has a zircon-type structure and has attracted attention due to its redox activity as photocatalyst[65][66][67]. Its space group I4 1 {amd was retrieved as the second scored one.…”
mentioning
confidence: 99%